An Insight Into the Delivery of a Palliative Approach in Residential Aged Care. The General Practitioner Perspective. - Phillips, J.; Davidson, Patricia; Willcock, S. (Sage Publishing, 2009)
Managing the complex care needs of older people is a global concern. General practitioners (GPs) play a pivotal role in aged care, yet little is known about their capacity to provide palliative care in nursing homes. This study aimed to investigate GPs' perceptions and understanding of a palliative approach. A convenience sample of rural GPs (n=13) participated in a series of three focus groups undertaken in August, 2005. These focus groups were all audio-taped, transcribed, and analysed using thematic content analysis. Four key themes emerged: uncertainty about a palliative approach, a need to reorientate providers, the challenges of managing third parties, and making it work and moving forward. These prelininary findings suggest that integrating a palliative approach in aged care requires GPs to have a great awareness of this paradigm and to be more effectively engaged in multidisciplinary care planning.